POLICY CHANGE IN SISTER CITY COOPERATION POLICY BETWEEN SEMARANG CITY AND BRISBANE CITY IN 2018-2023 - Himawan Bagas Wirastomo; Dyah Lituhayu (Journal of Public Policy and Management Review, 2020)
The sister city cooperation policy between Semarang City and Brisbane City is a policy that has been running for 25 years (as of 2018). This policy has a problem in the form of no output generated even though it has been running for 25 years. However, in 2018 the sister city cooperation policy by the Semarang City Government and the Brisbane City Government was decided to continue until 2023 with the signing of a Memorandum of Understanding agreed by both parties. Based on these explanations, this study aims to find out why the sister city cooperation policy was continued even though there was no output generated from this collaboration for 25 years. This study uses qualitative research methods with data sources derived from interviews with informants determined through snowball sampling with the Subdivision of Inter-Institution Cooperation Sub-District of Semarang City as the key informant. The results showed that there was a policy change that occurred in this sister city cooperation policy, namely the regulation that was used as the legal basis for implementing sister city cooperation and the field of cooperation that was mutually agreed upon by the Semarang City Government and the Brisbane City Government. It was also found that there were factors causing the continuing sister cooperation policy between the two cities which included internal factors and external factors. The internal factor in question is the initiative of the Semarang City Government to continue this policy for various reasons. While the external factor is an appeal from the Central Government to optimize sister city cooperation that already exists as a result of new regulations. In addition, there was no urgency to stop this collaboration because it tended to benefit the City of Semarang. The policy changes that occurred did not make the implementation run optimally so that it did not affect the development of Semarang. But the sister city cooperation has a role as an intermediary with Toyama which has an impact on the development vision of Semarang regarding the city pays attention to the environment through the cooperation of gas fuel conversion on BRT Semarang.